Stalemate Over Steel Orchestra - Joseph, Terry (Trinidad Express)
The article gives detail about Pan Trinbago’s eﬀort to launch a National Steel Orchestra and the procedures and arrangements made to have it possible.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Pan Trinbago (Organization); Steel band music -- Trinidad and Tobago